Koli children dressed for the procession - Mumbai Archive Project Team (Jio Institute, 2024)
The procession starts from the temple around five in the evening, takes a round of Worli Koliwada, and returns to the temple around three in the morning. Koli children dress up for the occasion and join the procession.